Macroeconomic factors that effect the exchange rate fluctuation in Malaysia / Syed Hazim Syed Zainul Abidin - Syed Zainul Abidin, Syed Hazim (2021)
This paper empirically investigates the macroeconomic factors that influence exchange rate fluctuation in Malaysia. The independent variables for this study are focus on macroeconomic factors that consists of employment rate, balance of payment, budget deficit or surplus, tax rate and corruption while dependent variable is exchange rate. The methodology applied for this study is using the Ordinary Least Square (OLS) method. The estimation data for this study covering the period quarterly between 2009 until 2019. The study had found that all variables except tax rate and budget deficit influence had an effect negatively towards exchange rate. Hence, tax rate and budget deficit showed significant effect on exchange rate. This was because tax rate effected on the cost of trade, import, export, and the economy of certain countries. Meanwhile, the budget deficit effect the government funding thus effect the economy, people and business owner.